Editorial - Apivatthakakul, Theerachai (Journal of Southeast Asian Orthopaedics, 2022)
The Thai Journal of Orthopaedic Surgery Volume 44 / Number 3-4 July-October 2020 is continue to published in this period of the COVID-19 pandemic. Many countries have the second wave of the pandemic, however, the situation in Thailand is really successful in control of the disease and the academic activity is gradually return. The operation has coming back to normal both the elective and emergency cases. The RCOST 2020 meeting was held at the Royal Cliff Beach as usual with the number register participant of almost 2,000. The onsite meeting and online meeting is possible for all RCOST members. This issue in your hand consists of several interesting articles with 2 case report and 4 original papers. In this issue including the minimally invasive medial hip approach, the outcomes of short stem total hip arthroplasty, the technique of tendon repair and spine surgery. Our journal is making progress in a positive way with supporting from the RCOST committee and all RCOST members who submit their valuable work in Orthopaedic field to demonstrated the up to date knowledge and skill or basic knowledge of Administration system to improve national policy in treating Orthopaedic patients. We hope we will pass this pandemic in very near future and setup not only the new normal for life but also for the new normal treatment for our patient.